Perception of the acoustic environment and neuroimaging findings: a report of six cases with a history of closed head injury. - Bergemalm P; Hennerdal S; Persson B; Lyxell B; Borg E (Acta Oto-Laryngologica, 2009)
Conclusion: The main finding was the relation between difficulty in determining the direction of movement of a sound source and frontal lesions and poor working memory. Poor correspondence in some cases between functional findings and imaging findings can be due to the possibility of axonal degeneration as well as plastic reorganization. Objective: The purpose of the present investigation of six cases was to identify auditory, cognitive and neuroimaging long-term sequelae of closed head injury (CHI) with particular focus on environmental sound recognition and moving sound sources. Subjects and methods: Six subjects who had experienced CHI were investigated with auditory tests. Four subjects also completed cognitive testing. CT and MRI were performed. Results: There was a large individual variability of the test results with respect to morphological findings. In five cases with central auditory processing disorders morphological brain damage was demonstrated. Two cases with shortcomings on cognitive testing and with frontal brain lesions demonstrated problems in determining the direction of movement of a sound source. The results may indicate that basal frontal lobe structures play a role in following and determining the direction of movement of a sound source. Two cases had problems with environmental sound recognition; in one left temporal brain lesions were demonstrated.